Impacto de la tecnología Blockchain en la auditoría financiera en Colombia (2023)
This scientific article explores the impact of Blockchain on financial auditing in the industrial sector of the municipality of Duitama Boyacá. The problem of traditional auditing is raised and how this innovative technology can provide solutions to improve transparency, security, effectiveness and efficiency in accounting and financial verification processes in companies. Thus helping the financial audit to have greater control, verification of movements, transactions that are carried out at the desired time and that cannot be easily modified without first being notified to all participants in this security chain, supported of nodes in the network that allows different devices from the same company to be connected, allowing information to be exchanged, performing tasks more quickly and accurately.